The effect of fasting during Ramadan towards improvement of type 2 Diabetes mellitus - Othman, Noratikah; Jusoh, Nurul Najwa; Jamaludin, Thandar Soe Sumaiyah (2019)
Introduction: Globally, the number of people with diabetes has been increasing trend in this modern day. Thus, this study aimed to explain the main factors of Type 2 Diabetes Mellitus (T2DM), to compare the random or fasting blood sugar before, during and after fasting month (Ramadan), and to determine the association between fasting and improvement of T2DM. Method: The total respondents of this study were 58 patients from Medical Outpatient Department. This study was used retrospective cohort study design. The data collected and recorded based on the inclusion and exclusion criteria. The fasting blood sugar for before, during and after the month of Ramadan was recorded in the designed form. The data were analysed by using SPSS version 20. Results: There were three factors of T2DM, obesity, smoking, and family history. There was no significant change of fasting blood glucose result for the comparison of three periods of time except one pair with p value of less than 0.05. There were no significant for the association between fasting and improvement of T2DM. In this study, researcher states that <0.05 was significant pvalue. Conclusion: This study concluded that there was no association between fasting and T2DM. This might be related to many factors such as the behaviour and disciplined of people in desire of consuming food and limited data collection.